2013
DOI: 10.1210/en.2012-1683
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hypoxia Increases the Susceptibility of Adult Rat Male Offspring to High-Fat Diet-Induced Nonalcoholic Fatty Liver Disease

Abstract: Exposure to an adverse intrauterine environment increases the risk for adult metabolic syndrome. However, the influence of prenatal hypoxia on the risk of fatty liver disease in offspring is unclear. The purpose of the present study was to evaluate the role of reduced fetal oxygen on the development and severity of high-fat (HF) diet-induced nonalcoholic fatty liver disease (NAFLD). Based on design implicating 2 factors, ie, maternal hypoxia (MH) and postnatal HF diet, blood lipid and insulin levels, hepatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Through the catch-up growth, the prenatal hypoxia offspring had comparable weights to controls after 1 month old. Consistent with previous reports, 22,23 the present study showed that more weight gain was found in the HF-exposed offspring, which might be due to significantly increased caloric intake. In addition, the offspring with both prenatal hypoxia and postnatal hyper-caloric HF diets showed much higher triacylglycerol, cholesterol, low-density lipoprotein-cholesterol, and free fatty acids in circulation, suggesting that the synergistic effects of prenatal hypoxia and postnatal HF diet were associated with an early onset of dyslipidemia in this model.…”
Section: Effect Of Prenatal Hypoxia and Postnatal Hf Diet On Lipid supporting
confidence: 93%
“…Through the catch-up growth, the prenatal hypoxia offspring had comparable weights to controls after 1 month old. Consistent with previous reports, 22,23 the present study showed that more weight gain was found in the HF-exposed offspring, which might be due to significantly increased caloric intake. In addition, the offspring with both prenatal hypoxia and postnatal hyper-caloric HF diets showed much higher triacylglycerol, cholesterol, low-density lipoprotein-cholesterol, and free fatty acids in circulation, suggesting that the synergistic effects of prenatal hypoxia and postnatal HF diet were associated with an early onset of dyslipidemia in this model.…”
Section: Effect Of Prenatal Hypoxia and Postnatal Hf Diet On Lipid supporting
confidence: 93%
“…Furthermore, HFD feeding alone increased markers of hepatic injury, as seen with oil red o staining and enzyme markers of hepatic injury in our study, with no difference between IUGR-HFD and Con-HFD. Similarly, maternal hypoxia increased fatty liver in HFD fed mice (15). HFD feeding alone decreased proteins involved in de novo cholesterol synthesis, LDL-C uptake from blood, and export of HDL-C and VLD-C export to the blood.…”
Section: Articlesmentioning
confidence: 87%
“…Diets high in salt and sugar are common in western communities as are diets high in fat. Increased incidence of fatty liver (Su et al, 2013;Gardebjer et al, 2017), cardiovascular pathology (Rueda-Clausen et al, 2012), adrenal sensitivity (He et al, 2017) and metabolic syndrome (Rueda-Clausen et al, 2011) have all been demonstrated with a prenatal perturbation in combination with a postnatal diet high in fat.…”
Section: The Second Hit Hypothesismentioning
confidence: 99%
“…Following maternal hypoxia of 10±1% oxygen from day 7 of pregnancy, rat offspring fed a high fat diet had increased plasma triglycerides, altered response to a glucose tolerance test and more severe non-alcoholic fatty liver disease (Su et al, 2013).…”
Section: The Second Hit Hypothesismentioning
confidence: 99%